Children's Motives for Admitting to Prosocial Behavior - Watanabe, Yayoi (Front Psychol, 2016)
There has been extensive research on children's moral evaluation of lying in prosocial situations. Current knowledge regarding the concept of lying has been derived from studies showing that cultural differences exist, whereby non-Western children tend to rate lie telling more positively than Western children do. These findings suggest that there are different views about whether children should publicize their prosocial behaviors and that children have universal motives when they admit to engaging in prosocial behavior. A gender difference has also been found in relation to prosocial behavior. However, previous studies did not investigate in detail children's motives for admission or non-admission to prosocial behavior, and if there is a gender difference. Therefore, this study examined the diversity in and development of motives for admitting or not admitting to engaging in prosocial behavior, with the aim of clarifying these behaviors as a function of children's grade level in school, and how such motives differ with age and gender. Questionnaires from 1345 elementary and junior high school students in Japan were analyzed. Results showed that children's communication tendency with regard to prosocial behavior reports peaked in the fourth grade of elementary school and gradually decreased thereafter. From the third grade of elementary school onwards, children reported that they refrained from admitting prosocial behaviors. Younger children more likely cited honesty as a crucial motive for admitting to prosocial behaviors. Girls were more likely to endorse honesty as a motive than boys were. Moreover, among younger children, girls feared others' negative evaluation and wanted to comply with modesty norms when not admitting. Further research is needed to examine the developmental process for motives behind prosocial behaviors.